2002
DOI: 10.1128/aem.68.11.5685-5692.2002
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Soil Ammonium Concentration on N 2 O Release and on the Community Structure of Ammonia Oxidizers and Denitrifiers

Abstract: The effect of ammonium addition (6.5, 58, and 395 g of NH 4 ؉ -N g [dry weight] of soil ؊1 ) on soil microbial communities was explored. For medium and high ammonium concentrations, increased N 2 O release rates and a shift toward a higher contribution of nitrification to N 2 O release occurred after incubation for 5 days at 4°C. Communities of ammonia oxidizers were assayed after 4 weeks of incubation by denaturant gradient gel electrophoresis (DGGE) of the amoA gene coding for the small subunit of ammonia mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
169
8
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(198 citation statements)
references
References 42 publications
(41 reference statements)
19
169
8
2
Order By: Relevance
“…In the N treatment, the AOB community composition was significantly altered by ammonium addition in both soils. However, our result was inconsistent with previous study of Avrahami et al (2002) who reported that agricultural soils did not show any AOB community shifts under ammonium treatment with 4-6 weeks of incubation. This inconsistency might be attributed to higher ammonium level in our study, which could promote the growth of AOB in soils (Jia and Conrad 2009;Cui et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…In the N treatment, the AOB community composition was significantly altered by ammonium addition in both soils. However, our result was inconsistent with previous study of Avrahami et al (2002) who reported that agricultural soils did not show any AOB community shifts under ammonium treatment with 4-6 weeks of incubation. This inconsistency might be attributed to higher ammonium level in our study, which could promote the growth of AOB in soils (Jia and Conrad 2009;Cui et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…However, at T2, bands 'h' and 'i 0 were most prominent in the AOB amoA community profile (Figure 3c). Sequence analysis revealed that all detected AOB amoA bands were affiliated with several sequence clusters within Nitrification in zinc-contaminated soil J Mertens et al the Nitrosospira lineage (Avrahami et al, 2002), and no clustering of sequences was observed with respect to the Zn tolerance of the community (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also showed that ammonium, fertilization, plant species, sampling time, water logging and temperature all temporarily altered the structure of nirK-harboring denitrifying community (Avrahami et al, 2002;Braker et al, 2010;Bremer et al, 2007;Wolsing and Priemé, 2004;Yoshida et al, 2009). The genetic shifts of the denitrifying community due to PAHs perturbation could be attributed to the inhibition of sensitive and the development of tolerant species (Leahy and Colwell, 1990;Ford, 1993;Whittaker, 1975).…”
Section: Shifts In Diversity and Composition Of The Denitrifying Commmentioning
confidence: 91%